Kecemasan Pada Anak Prasekolah - Azam, Muhammad Nazif (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2020)
Anxiety is a part of every child's development. Anxiety can arise because of the attitude of parents who are too protective of children. That causes the child to need to worry if he is not with his parents and afraid that his friends will hurt him. This study aims to describe the level of difficulty of preschoolers in Magelang. This research uses quantitative descriptive methods. Samples in this study were taken 108 respondents, who were taken by random sampling technique. Data collection uses questionnaires with items about participation categories. The results showed that 45.4% of children belonged to the general discussion group, 36.1% were in the social insurance category, 44.4% were included in the category of obsessive compulsive difficulties, 43.5% challenges of physical injury, and 38% of children would be it's hard to separate from parents. Then it can be seen on average from the scale that has been answered by respondents, as many as 26.9% of children who use physical difficulties done by others against them, even though it is not certain to happen to them.